L & D's playbook for the digital age - Carson, Brandon (ASTD, the Association for Talent Development, 2021)
In this book, You'll learn new technology and digital strategies which are integrated, and the workers at all levels will be required to build capability much faster than before, navigating more complex systems and processes. --